ロス トウ ロイド ミサキ ナンキョク ロガン タイ ノ ケイソウ ショクセイ - 福島, 博; フクシマ, ヒロシ; FUKUSHIMA, Hiroshi (国立極地研究所, 1964)
P(論文) When the writer visited the McMurdo Station in December, 1962, as an observer of the United States Antarctic Research Program, the writer had an opportunity of investigating fresh-water algae at Cape Royds on December 10, 1962. W. & G. S. WEST made a thesis on the algae at Cape Royds in 1911 however, the present writer reports the results of his own investigation below. As the writer, on the occasion of his expedition, was given kind cooperation from Dr. T. O. JOHNES, Mr. E. E. GOODALE of U. S. A. R. P., Dr. TAKESHI NAGATA and Dr. TETSUYA TORII, the writer wishes to express his sincere thanks to them. According to the map, there are about 9 lakes at Cape Royds, but the writer investigated 9 lakes, among which 5 were discribed on the map, but 2 not described. (Fig. 1) From these lakes, the writer collected 29 materials and made microscopic examination. The table 1 shows the correlation of circumstantial factors of every lake and growing of algae in groups. Judging from the above table 1, in fresh-water lake (Cl' 123 mg/l), growing was Navicula muticopsis association in brackish lake with little salt content (Cl' ca. 1 g/l), it was Tropidoneis laevissima association and in brackish lake with much salt content (Cl' ca. 3 g/l), it was Nitzschia sp. association. The correlation of salt content of lake water and Navicula muticopsis association and Tropidoneis laevissima association showed the same tendency to what the writer observed at Sinnan Rock at Prince Olav Coast in 1962. Among the 19 kinds of algae which were found at Cape Royds, 12 kinds were endemic species and 7 kinds were cosmopolitan species. Endemic species were more than cosmopolitan species, holding 63% of the whole number. Preferential species were all endemic ones. On the algae around Syowa Base, proportion of endemic species in all the algae at the Syowa Base was not so large and cosmopolitan species were apt to become more superior ones than endemic ones. Syowa Base is at approx. 69°S and McMurdo Station is at approx. 78°S. The ...